Follow-up after radioiodine remnant ablation in differentiated thyroid cancer: the view of nuclear medicine physician - A. Yu. Shurinov; E. V. Borodavina (Опухоли головы и шеи, 2023)
Timeliness of accurate dynamic observation and a clear understanding of the treatment response guarantees health of patients with differentiated thyroid cancer. Multidimensional approach to evaluation of thyroid-stimulating hormone, tumor markers, ultrasound picture, as well as results of molecular imaging with radioactive iodine is clearly defined in international clinical guidelines. At the A.F. Tsyb Medical Radiological Research Center – branch of the National Medical Research Radiological Center for more than 15 years tactics of control exam 6 months after radioactive iodine ablation has been implemented. The aim of the current article is to consider the sequence of diagnostic search for different responses to treatment of differentiated thyroid cancer.